2012
DOI: 10.1002/psc.2437
|View full text |Cite
|
Sign up to set email alerts
|

The insect peptide CopA3 inhibits lipopolysaccharide‐induced macrophage activation

Abstract: We recently demonstrated that the insect peptide CopA3 (LLCIALRKK), a disulfide-linked dimeric peptide, exerts antimicrobial and anti-inflammatory activities in a mouse colitis model. Here, we examined whether CopA3 inhibited activation of macrophages by LPS. Exposure of an unseparated mouse peritoneal cell population or isolated peritoneal macrophages to LPS markedly increased secretion of IL-6 and TNF-α; these effects were significantly inhibited by CopA3 treatment. The inhibitory effect of CopA3 was also ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Zhu et al reported that GNPs significantly attenuated the rise in ROS/RNS-mediated inflammatory responses [43]. Similar to the previous findings, our preliminary study also indicated that CopA3 inhibited the NO production in LPS-stimulated RAW264.7 cells ( Supplementary Figure 2A) [27]. Therefore, in our study, the effective inhibition of GNP-CK-CopA3 in LPS-induced production of NO and overexpression of mRNA and protein of pro-inflammatory cytokines was probably due to the combined role of both CopA3 and nanoparticles.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Zhu et al reported that GNPs significantly attenuated the rise in ROS/RNS-mediated inflammatory responses [43]. Similar to the previous findings, our preliminary study also indicated that CopA3 inhibited the NO production in LPS-stimulated RAW264.7 cells ( Supplementary Figure 2A) [27]. Therefore, in our study, the effective inhibition of GNP-CK-CopA3 in LPS-induced production of NO and overexpression of mRNA and protein of pro-inflammatory cytokines was probably due to the combined role of both CopA3 and nanoparticles.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported to exert antibacterial effects against various pathogenic bacteria [24] and selective anticancer on human gastric cancer cells [25]. CopA3 also ameliorated inflammatory responses in the gut [26] and lipopolysaccharide (LPS)induced macrophage activation [27].…”
mentioning
confidence: 99%
“…conspicillatum may defend itself against invading pathogens by developing strong antimicrobial compounds, among them HDP. Only a few HDP have been identified from a limited number of Coleopteran dung species, which include Copris tripartitus , with the CopA3 peptide [ 23 ] and Onthophagus taurus [ 24 ]. Therefore, the purpose of this study was to identify and functionally characterize new HDP from the O .…”
Section: Introductionmentioning
confidence: 99%
“…Then, we prepared a dimeric form of CopA3 through a disulfide linkage and investigated its anti-inflammatory activities in LPS-induced macrophages. Coprisin and dimer CopA3 inhibited the expression of proinflammatory cytokines in LPS-activated Raw264.7 cells and/or mouse peritoneal macrophages [26,27]. Allomyrinasin and the aforementioned peptides are CAPs, which share common features such as a…”
Section: Allomyrinasin Reduces the Expression Of Proinflammatory Cytomentioning
confidence: 99%